Hubungan Kecerdasan Emosi dengan Kemampuan Coping Adaptif - Saptoto, Ridwan (Faculty of Psychology, Universitas Gadjah Mada, 2010)
This study was aimed to analyze the correlation between adaptive coping and emotional intelligence (EI). The subject of this study (N=69) are high school students in SMU Negeri 8 Yogyakarta, whose age ranged from 15 to 17 years old. Adaptive coping is measured by adaptive coping scale, and EI is measured by EI scale. Researcher developed both scale. Data was analyzed using Pearsonâ€™s product moment correlation. Results show that there are: positive correlation between EI and problem focused coping (PFC) part I (r=0,302; p=0,006), negative correlation between EI and emotional focused coping (EFC) and confrontative coping (CC) part I (r=â€0,322; p=0,004), and negative correlation between EI and PFC and CC part II (r=â€0,366; p=0,001). Spearmanâ€™s test correlation used to analyze correlation between EI and EPC part II, because this correlation did not meet linearity assumption. Spearmanâ€™s test correlation show that there is no correlation between EI and EPC part II (p=0,337). Based on these minor hypothesis, it is concluded that generally there is correlation between EI and adaptive coping ability.